2023
DOI: 10.1021/acs.est.3c01094
|View full text |Cite
|
Sign up to set email alerts
|

Linking Transthyretin-Binding Chemicals and Free Thyroid Hormones: In Vitro to In Vivo Extrapolation Based on a Competitive Binding Model

Abstract: Large numbers of pollutants competitively inhibit the binding between thyroid hormones and transthyretin (TTR) in vitro. However, the impact of this unintended binding on free thyroid hormones in vivo has not yet been characterized. Herein, we established a quantitative in vitro to in vivo extrapolation (QIVIVE) method based on a competitive binding model to quantify the effect of TTR-binding chemicals on free thyroid hormones in human blood. Twenty-five TTR-binding chemicals including 6 hydroxyl polybromodiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…As early as 1999, it was found that OH-PCBs exhibited TH-like affinity to serum TTR in vitro , suggesting a potential inhibition of TH transport in vivo . Quantitative models also showed that OH-PCBs may competitively bind with TTR, resulting in aggregation of FTHs . The presence of OH-PCBs also suppressed T3-induced transcriptional activation of TRs and led to aggression of T3 in Japanese macaque ( Macaca fuscata ) .…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1999, it was found that OH-PCBs exhibited TH-like affinity to serum TTR in vitro , suggesting a potential inhibition of TH transport in vivo . Quantitative models also showed that OH-PCBs may competitively bind with TTR, resulting in aggregation of FTHs . The presence of OH-PCBs also suppressed T3-induced transcriptional activation of TRs and led to aggression of T3 in Japanese macaque ( Macaca fuscata ) .…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of normal THs levels in serum can impact the development of the central nervous system, especially during fetal development, and is associated with neurological disorders including Alzheimer’s disease (AD) . Epidemiological studies have revealed an association between exposure to thyroid hormone disrupting chemicals (TDCs) and the increased risk of thyroid-related diseases. Transthyretin (TTR) is a major thyroxine (T 4 ) transport protein in serum that has been demonstrated to mediate the toxicity of many TDCs. , TDCs can compete with endogenous T 4 for binding to TTR, which can lead to the increased clearance of free T 4 and the disruption of TH homeostasis. In addition to TH disruption, binding to TTR can also mediate the transport of chemical pollutants across placental and blood–brain barriers into various compartments ( e.g., fetus and brain), which may induce a multitude of adverse effects. Thus, the identification of environmental chemicals binding to TTR is important for understanding their potential health risks.…”
Section: Introductionmentioning
confidence: 99%
“…5−7 Transthyretin (TTR) is a major thyroxine (T 4 ) transport protein in serum that has been demonstrated to mediate the toxicity of many TDCs. 8,9 TDCs can compete with endogenous T 4 for binding to TTR, which can lead to the increased clearance of free T 4 and the disruption of TH homeostasis. 9−11 In addition to TH disruption, binding to TTR can also mediate the transport of chemical pollutants across placental and blood−brain barriers into various compartments (e.g., fetus and brain), which may induce a multitude of adverse effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Specifically, displacement of TH from TTR may result in reduced delivery of TH to target tissue and disruption of pathways dependent on TH activation . TH displaced from TTR may also be metabolized and excreted resulting in decreased serum TH levels . Due to the limited amount of data on binding activities of compounds to TTR, only a few computational studies are reported in the literature.…”
mentioning
confidence: 99%
“…This data set has been split into a training set (1012 compounds) as well as leaderboard set (200 compounds) and a blind set (300 compounds). The compounds from previous studies ,, that overlapped with molecules in the challenge data set were mainly used as part of the training set. It should be mentioned that some compounds are mixtures, while others are salts, and some contain metals.…”
mentioning
confidence: 99%